La refondation architecturale de la Cour de justice européenne à Luxembourg - Lorenzo Diez; Dominique Perrault (In Situ)
The European Court of Justice is in Luxembourg since 1973, in a group of buildings constructed and transformed little by little over the last 50 years. At the heart of what has become an urban complex, stands the original courthouse, the work of architects Jean-Paul Conzemius, François Jamagne and Michel Van der Elst. In 2008, the architect Dominique Perrault restructured the palace and extended it by enveloping it with an “architectural ring”. This article presents, firstly, the original structure, a unique example of metallic architecture from the end of the 20th century by explaining the principles of its composition and its construction, its spatialities and its materialities as well as its symbolic qualities. It then proposes a reflection upon the 2008 intervention and the ring that led to a redesign of the palace’s architecture. Finally, it shines a light on the promising innovation introduced by its label as “Outstanding Contemporary Architecture”, namely the possibility, through the label’s sliding 100-year period, of superimposing the theories and practices of architectural creation and conservation.